BaAl1.4Si0.6O3.4N0.6:Eu2+ green phosphorsâ€™ application for improving luminous performance - My Hanh Nguyen Thi; Nguyen Le Thai; Thuc Minh Bui; Tam Nguyen Kieu (International Journal of Electrical and Computer Engineering (IJECE), 2023)
The molten salt synthesis (MSS) method was used to effectively prepare green phosphors BaAl1.4Si0.6O3.4N0.6:Eu2+ (or BSON:Eu2+) via one homogeneous sphere-like morphology utilizing NaNO3 in the form of the reacting agent. The phosphors produced one wide stimulation spectrum between 250 and 460 nm, as well as a significant green emission has a maximum point at 510 nm owing to the 4f65d1-4f7 (8S7/2) shifts for Eu2+ ions. With illumination under 365 as well as 450 nm, the ideal discharge strengths for the specimen prepared utilizing melted salt would receive a boost of 17% and 13%, surpassing the specimen prepared utilizing the traditional solid-state reaction (SSR) approach. The abatement of concentration for the ions of Eu2+ from BSON:Eu2+ is 5 mol%. In addition, the interactivity of dipole-dipole would be the cause of said abatement. Heat abatement would be studied utilizing the formation coordinate method with abatement temperature reaching âˆ¼200 oC. Elemental mapping as well as power-dispersing X-ray spectroscopy (EDS) spectra demonstrated that the expected BaAl1.4Si0.6O3.4N0.6:Eu2+ materials were formed.